Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f
[a, b]
g(x) (a, b)
f [a; b]
x ∈ (a; b) f(a) = f(b)
c ∈ (a; b) f
(c) = 0
f [a; b]
f [a; b]
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
x
1
, x
2
∈ (a; b)
f(x
1
) = min
[a;b]
f(x) = m, f (x
2
) = max
[a;b]
f(x) = M.
a) m = M. f(x) = const [a; b] f
(x) = 0
x ∈ (a; b) c
b) m < M f(a) = f(b)
x
1
, x
2
[a; b]
x
1
∈ (a; b) 0
(a; b) c f
(c)
f(x) = 2 −
3
√
x
2
, x ∈ [−1; 1] f(x) f(x)
(−1; 1) f(−1) = f(1) f
(x) = −
2
3
3
√
x
x
0
= 0 ∈ (−1; 1)
[a; b] f(x)
f(x) (a; b)
f(x) =
1, x = 0,
x, 0 < x ≤ 1.
x = 0 x
0
∈ (0, 1)
f
(x
0
) = 0.
y = f(x), ∀x ∈ [a; b]
M(c; f(c)), c ∈ (a; b) Ox
f(x) (a; b)
f(x) = 0 n (a; b)
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f
(x) = 0 n − 1 (a; b).
f
(k)
(x) = 0 n − k
(a; b) k = 1, 2, . . . , n
f(x) = 0 n
(a; b) x
1
< x
2
< ··· < x
n
n − 1 [x
1
; x
2
], [x
2
; x
3
], . . . , [x
n−1
; x
n
]
f
(x) = 0 n − 1 n − 1
(x
1
; x
2
), (x
2
; x
3
), . . . , (x
n−1
; x
n
) n − 1 ξ
1
, ξ
2
, . . . , ξ
n−1
f
(ξ
1
) = f
(ξ
2
) = ··· = f
(ξ
n−1
) = 0.
n −2 (ξ
1
; ξ
2
), . . . , (ξ
n−2
; ξ
n−1
)
f
(x) = 0 n − 2 (a; b).
k f
(k)
(x) = 0
n − k (a; b).
f(x) [a; b]
(a; b) f
(x) = 0
n −1 (a; b) f(x) = 0
n
f(x) = 0 n
(a; b) n + 1
1.1 f
(x) = 0 n (a; b)
f(x) = 0 n
(a; b)
f(x)
f(x) n (n ≥ 1)
[a; b].
f(x) n + 1 (a; b).
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f(a) = f
(a) = ··· = f
(n)
(a) = 0, f(b) = 0.
b
1
, b
2
, . . . , b
n+1
(a; b)
f
(k)
(b
k
) = 0, k = 1, 2, . . . , n + 1.
f(a) = f(b) = 0,
b
1
∈ (a; b) f
(b
1
) = 0, f
(a) = 0,
b
2
∈ (a; b
1
) ⊂ (a; b) f
(b
2
) = 0.
f
(a) = 0 f
(b
3
) = 0
b
3
∈ (a; b
2
) ⊂ (a; b).
n b
n
∈ (a; b
n−1
) ⊂ (a; b)
f
(n)
(b
n
) = 0, f
(n)
(a) = 0,
b
n+1
∈ (a; b
n
) ⊂ (a; b) f
(n+1)
(b
n+1
) = 0.
b
1
, b
2
, . . . , b
n+1
(a; b)
f
(k)
(b
k
) = 0, k = 1, 2, . . . , n + 1.
f
[a; b] (a; b).
c ∈ (a; b)
f(b) − f(a) = f
(c)(b − a).
F (x) = f(x) − λx,
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
λ F (a) = F (b)
f(a) − λa = f (b) − λb.
λ =
f(b) − f(a)
b − a
.
F (x) [a; b],
(a; b) F(a) = F (b), c ∈ (a; b)
F
(c) = 0. F
(x) = f
(x) − λ
F
(c) = 0 ⇔ f
(c) − λ = 0 ⇔ f
(c) = λ.
λ f
(c) =
f(b) − f(a)
b − a
,
f(b) − f(a) = f
(c)(b − a).
f(a) = f (b)
f(x)
y = f (x)
M(c; f(c))
AB A(a; f(a)) B(b; f(b))
f : [a; b] −→ R f
(x) = 0
x ∈ (a; b) f = const [a; b].
x
0
∈ (a; b)
x (a; b) [x
0
; x] [x; x
0
]
(a; b) f
f(x) − f(x
o
) = f
(c)(x − x
0
), ∀c ∈ (x
o
; x).
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f
(x) = 0 x ∈ (a; b) f
(c) = 0
c ∈ (x
0
; x) f(x) = f(x
0
)
f(x) x ∈ (a; b)
f = const [a; b].
f(x) g(x)
[f(x) − g(x)]
= f
(x) − g
(x) = 0.
f(x) −g(x) = C (C = const) f(x) = g(x) + C
f, g
[a; b] (a; b), g
(x) = 0
x ∈ (a; b). c ∈ (a; b)
f(b) − f(a)
g(b) − g(a)
=
f
(c)
g
(c)
.
g(b) = g(a) g(b) = g(a)
g(x)
c ∈ (a; b) g
(c) = 0
g
(x) = 0, ∀x ∈ (a; b).
F (x) = f(x) − λg(x),
λ F (a) = F (b)
f(a) − λg(a) = f (b) − λg(b).
λ =
f(b) − f(a)
g(b) − g(a)
.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
F (x) ∃c ∈ (a; b)
F
(c) = 0. F
(x) = f
(x) − λg
(x)
F
(c) = 0 ⇔ f
(c) − λg
(c) = 0 ⇔ λ =
f
(c)
g
(c)
.
f(b) − f(a)
g(b) − g(a)
=
f
(c)
g
(c)
.
g(x) = x.
[a, b]
min
[a,b]
f(x), max
[a,b]
f(x)
.
f(x) [a; +∞)
(a; +∞) lim
x→+∞
f(x) = f (a). c ∈ (a; +∞)
f
(c) = 0
f(x) = f(a) x > a c
a
b > a f(b) = f (a) f(b) > f(a)
µ (f(a); f(b)),
α ∈ (a; b) f(α) = µ lim
x→+∞
f(x) = f(a) < µ
d > b f(d) < µ. f(x) [a; +∞)
β ∈ (b; d) f(β) = µ = f(α),
c ∈ (α; β) f
(c) = 0.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
I(a; b) ⊂ R
(a; b), [a; b), (a; b] [a; b] a < b.
f(x) I(a; b) ⊂ R
x
1
, x
2
∈ I(a; b) x
1
< x
2
f(x
1
) ≤ f(x
2
)
f(x) I(a; b).
x
1
, x
2
∈ I(a; b) x
1
< x
2
f(x
1
) < f (x
2
) f(x)
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
I(a; b).
x
1
, x
2
∈ I(a; b) x
1
< x
2
f(x
1
) ≥
f(x
2
) f(x) I(a; b).
x
1
, x
2
∈ I(a; b) x
1
< x
2
f(x
1
) > f(x
2
) f(x)
I(a; b).
I(a, b)
I(a; b) I(a; b)
I(a; b).
(a; b)
y = f (x) (a; b).
f
(x) > 0 x ∈ (a; b) y = f (x)
f
(x) < 0 x ∈ (a; b) y = f(x)
x
1
, x
2
(x
1
< x
2
) (a; b)
f(x) (a; b) f (x) [x
1
; x
2
]
(x
1
; x
2
).
y = f(x) [x
1
; x
2
]
∃c ∈ (x
1
; x
2
)
f(x
2
) − f(x
1
) = f
(c)(x
2
− x
1
).
i) f
(x) > 0 (a; b) f
(c) > 0 x
2
−x
1
> 0
f(x
2
) − f(x
1
) > 0 f(x
2
) > f(x
1
), f(x)
(a; b)
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
ii) f
(x) < 0 (a; b) f
(c) < 0 x
2
−x
1
> 0
f(x
2
) − f(x
1
) < 0 f(x
2
) < f(x
1
), f(x)
(a; b)
y = f (x)
(a; b) f
(x) ≥ 0 f
(x) ≤ 0
(a; b) f(x)
f
(x) ≥ 0
(a; b) f
(x) = 0 x
1
∈ (a, b) f(x)
(a, x
1
) (x
1
, b) (a, x
1
] [x
1
, b)
(a, x
1
] [x
1
, b).
(a, b).
f(x) I(a; b) ⊂ R
x
1
, x
2
∈ I(a; b) α, β α + β = 1
f(αx
1
+ βx
2
) ≤ αf (x
1
) + βf(x
2
).
x
1
= x
2
f(x) I(a; b).
f(x) I(a; b) ⊂ R
x
1
, x
2
∈ I(a; b) α, β α + β = 1
f(αx
1
+ βx
2
) ≥ αf (x
1
) + βf(x
2
).
x
1
= x
2
f(x) I(a; b).
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
x
1
< x
2
x = αx
1
+ βx
2
α, β α + β = 1 (x
1
; x
2
)
α =
x
2
− x
x
2
− x
1
; β =
x − x
1
x
2
− x
1
.
f(x) I(a; b) f (x)
I(a; b) f
(x) I(a; b)
f(x) I(a; b) x
1
< x < x
2
(x, x
1
, x
2
∈ I(a; b))
x
2
− x
x
2
− x
1
> 0;
x − x
1
x
2
− x
1
> 0
x
2
− x
x
2
− x
1
+
x − x
1
x
2
− x
1
= 1.
f(x) ≤
x
2
− x
x
2
− x
1
f(x
1
) +
x − x
1
x
2
− x
1
f(x
2
)
⇔
f(x) − f(x
1
)
x − x
1
≤
f(x
2
) − f(x)
x
2
− x
.
x → x
1
f
(x
1
) ≤
f(x
2
) − f(x
1
)
x
2
− x
1
.
x → x
2
f(x
2
) − f(x
1
)
x
2
− x
1
≤ f
(x
2
).
f
(x
1
) ≤ f
(x
2
) f
(x)
f
(x) x
1
< x < x
2
(x, x
1
, x
2
∈ I(a; b)). x
3
, x
4
x
3
∈ (x
1
; x)
x
4
∈ (x; x
2
)
f(x) − f(x
1
)
x − x
1
= f
(x
3
),
f(x
2
) − f(x)
x
2
− x
= f
(x
4
).
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f
(x
3
) ≤ f
(x
4
)
f(x) − f(x
1
)
x − x
1
≤
f(x
2
) − f(x)
x
2
− x
,
f(x) ≤
x
2
− x
x
2
− x
1
f(x
1
) +
x − x
1
x
2
− x
1
f(x
2
).
f(x) I(a; b).
f(x) I(a; b) f(x)
I(a; b) f
(x) ≥ 0 (f
(x) ≤ 0) I(a; b).
2.3
I(a; b).
y = f (x) I(a; b)
f(x) = 0 I(a; b).
y = f(x)
I(a; b), f
(x) > 0 f
(x) < 0 I(a; b). f
(x)
I(a; b), f
(x) = 0
I(a; b). 1.2
f(x) = 0
{x
k
, y
k
∈
I(a; b), k = 1, 2, . . . , n}
x
1
≥ x
2
≥ ··· ≥ x
n
, y
1
≥ y
2
≥ ··· ≥ y
n
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
x
1
≥ y
1
,
x
1
+ x
2
≥ y
1
+ y
2
,
···
x
1
+ x
2
+ ··· + x
n−1
≥ y
1
+ y
2
+ ··· + y
n−1
,
x
1
+ x
2
+ ··· + x
n
= y
1
+ y
2
+ ··· + y
n
.
f(x) I(a; b)
f(x
1
) + f(x
2
) + ··· + f (x
n
) ≥ f(y
1
) + f(y
2
) + ··· + f (y
n
).
f(x
1
) ≥ f(y
1
) + f
(y
1
)(x
1
− y
1
), ∀x
1
, y
1
∈ I(a; b).
x
1
= y
1
.
⇔ f(x
1
) − f(y
1
) ≥ f
(y
1
)(x
1
− y
1
).
i) x
1
= y
1
ii) x
1
> y
1
x
1
− y
1
> 0
⇔
f(x
1
) − f(y
1
)
x
1
− y
1
≥ f
(y
1
).
⇔ f
(x
1
) ≥ f
(y
1
) y
1
< x
1
< x
1
.
f
(x) f
(x) > 0
iii) x
1
< y
1
x
1
− y
1
< 0
⇔
f(x
1
) − f(y
1
)
x
1
− y
1
≤ f
(y
1
).
⇔ f
(x
1
) ≤ f
(y
1
) x
1
< x
1
< y
1
.
f
(x) f
(x) > 0
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f(x
i
) ≥ f(y
i
) + f
(y
i
)(x
i
− y
i
), ∀x
i
, y
i
∈ I(a; b), i = 1, 2, . . . , n.
f(x
1
) ≥ f(y
1
) + f
(y
1
)(x
1
− y
1
),
f(x
2
) ≥ f(y
2
) + f
(y
2
)(x
2
− y
2
),
. . . . . . . . . . . . . . . . . . . . . . . . . . .
f(x
n
) ≥ f(y
n
) + f
(y
n
)(x
n
− y
n
).
n
i=1
f(x
i
) ≥
n
i=1
f(y
i
) +
n
i=1
f
(y
i
)(x
i
− y
i
)
⇔
n
i=1
f(x
i
) −
n
i=1
f(y
i
) ≥
n
i=1
f
(y
i
)(x
i
− y
i
).
n
i=1
f
(y
i
)(x
i
− y
i
).
a
i
= f
(y
i
) b
i
= (x
i
− y
i
)
n
i=1
f
(y
i
)(x
i
− y
i
) =
n−1
i=1
[f
(y
i
) − f
(y
i+1
)][(x
1
+ x
2
+ ··· + x
n−1
) − (y
1
+ y
2
+ ···
+ y
n−1
)] + f
(y
n
)[(x
1
+ x
2
+ ··· + x
n
) − (y
1
+ y
2
+ ··· + y
n
)].
f
(y
i
) − f
(y
i+1
) ≥ 0 f
(y)
(x
1
+ x
2
+ ··· + x
n−1
) − (y
1
+ y
2
+ ··· + y
n−1
) ≥ 0,
(x
1
+ x
2
+ ··· + x
n
) − (y
1
+ y
2
+ ··· + y
n
) = 0.
n
i=1
f
(y
i
)(x
i
− y
i
) ≥ 0.
n
i−1
f(x
i
) −
n
i−1
f(y
i
) ≥ 0,
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f(x
1
) + f(x
2
) + ··· + f (x
n
) ≥ f(y
1
) + f(y
2
) + ··· + f (y
n
).
ABC
δ
ABC
= max{A, B, C} − min{A, B, C}
δ
ABC
ABC.
δ
ABC
≥ 0 δ
ABC
= 0 ABC
A
1
B
1
C
1
A
2
B
2
C
2
max{A
1
, B
1
, C
1
} ≤ max{A
2
, B
2
, C
2
},
min{A
1
, B
1
, C
1
} ≥ min{A
2
, B
2
, B
2
}
A
1
B
1
C
1
A
2
B
2
C
2
A
1
B
1
C
1
A
2
B
2
C
2
A
1
B
1
C
1
A
2
B
2
C
2
A
1
≥ B
1
≥ C
1
, A
2
≥ B
2
≥ C
2
)
A
1
≤ A
2
, C
1
≥ C
2
, A
1
B
1
C
1
A
2
B
2
C
2
.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
y = f(x) f
(x)
(a; b).
f
(x) ≥ 0 x ∈ (a; b)
f(x) ≥ f(x
0
) + f
(x
0
)(x − x
0
), x, x
0
∈ (a; b).
f
(x) ≤ 0 x ∈ (a; b)
f(x) ≤ f(x
0
) + f
(x
0
)(x − x
0
), x, x
0
∈ (a; b).
A
2
B
2
C
2
A
1
B
1
C
1
f(x) f
(x) ≥ 0 x ∈ (0; π).
f(A
1
) + f(B
1
) + f(C
1
) ≥ f(A
2
) + f(B
2
) + f(C
2
).
f
(x) ≥ 0, ∀x ∈ (0; π) 2.1
f(x) ≥ f(x
0
) + f
(x
0
)(x − x
0
), ∀x, x
0
∈ (0; π).
A
1
≥ B
1
≥ C
1
, A
2
≥ B
2
≥ C
2
.
2.4 A
1
≥ A
2
C
1
≤ C
2
.
A
1
≥ A
2
,
A
1
+ B
1
≥ A
2
+ B
2
,
A
1
+ B
1
+ C
1
= A
2
+ B
2
+ C
2
.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f(A
1
) ≥ f(A
2
) + f
(A
2
)(A
1
− A
2
),
f(B
1
) ≥ f(B
2
) + f
(B
2
)(B
1
− B
2
),
f(C
1
) ≥ f(C
2
) + f
(C
2
)(C
1
− C
2
).
f(A
1
) + f(B
1
) + f(C
1
) ≥ f(A
2
) + f(B
2
) + f(C
2
)
+ [f
(B
2
) − f
(C
2
)][(A
1
+ B
1
) − (A
2
+ B
2
)]
+ [f
(A
2
) − f
(B
2
)](A
1
− A
2
)
≥ f(A
2
) + f(B
2
) + f(C
2
).
ABC α, β, γ
α + β + γ = 1.
A
0
= αA + βB + γC,
B
0
= αB + βC + γA,
C
0
= αC + βA + γB.
sin A + sin B + sin C ≤ sin A
0
+ sin B
0
+ sin C
0
.
A
0
+B
0
+C
0
= A + B +C = π A
0
, B
0
, C
0
A ≥ A
0
,
A + B ≥ A
0
+ B
0
,
A + B + C = A
0
+ B
0
+ C
0
.
A ≥ B ≥ C, A
0
≥ B
0
≥ C
0
.
f(x) = sin x, ∀x ∈ [0; π].
f
(x) = cos x, f
(x) = −sin x ≤ 0, ∀x ∈ [0; π].
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
2.1
f(x) ≤ f(x
0
) + f
(x
0
)(x − x
0
), ∀x, x
0
∈ [0; π].
sin A ≤ sin A
0
+ cos A
0
(A − A
0
),
sin B ≤ sin B
0
+ cos B
0
(B − B
0
),
sin C ≤ sin C
0
+ cos C
0
(C − C
0
).
sin A + sin B + sin C ≤ sin A
0
+ sin B
0
+ sin C
0
+ cos C
0
(A + B + C − A
0
− B
0
− C
0
)
+ (cos B
0
− cos C
0
)(A + B − A
0
− B
0
)
+ (cos A
0
− cos B
0
)(A − A
0
).
A + B + C − (A
0
+ B
0
+ C
0
) = 0; A + B ≥ A
0
+ B
0
; A ≥ A
0
,
π > B
0
≥ C
0
≥ 0 ⇒ cos B
0
≤ cos C
0
,
π > A
0
≥ B
0
≥ 0 ⇒ cos A
0
≤ cos B
0
,
sin A + sin B + sin C ≤ sin A
0
+ sin B
0
+ sin C
0
.
ABC
tan
A
2
+ tan
B
2
+ tan
C
2
≥ 2
√
2 − 1.
A ≥ B ≥ C.
A ≥
π
2
,
A + B ≥
π
2
+
π
4
,
A + B + C =
π
2
+
π
4
+
π
4
.
⇒
A
2
≥
π
4
,
A
2
+
B
2
≥
π
4
+
π
8
,
A
2
+
B
2
+
C
2
=
π
4
+
π
8
+
π
8
.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên
f(x) = tan x x ∈
0;
π
2
. f
(x) > 0, ∀x ∈
0;
π
2
.
2.1,
f(x) ≥ f(x
0
) + f
(x
0
)(x − x
0
), ∀x, x
0
∈
0;
π
2
.
2.1
tan
A
2
+ tan
B
2
+ tan
C
2
≥ tan
π
4
+ tan
π
8
+ tan
π
8
.
tan
π
8
=
√
2 − 1
tan
π
4
+ tan
π
8
+ tan
π
8
= 2
√
2 − 1.
tan
A
2
+ tan
B
2
+ tan
C
2
≥ 2
√
2 − 1.
Số hóa bởi Trung tâm Học liệu - Đại học Thái Nguyên